Analisis Pengaruh Modal Pribadi Dan Modal Pinjaman Terhadap Pendapatan Usaha Mikro Kecil Menengah (UMKM) Di Kota Kupang - Yusthin Putri Vania Djami; Fransina W. Ballo; Olivia L. E. Tomasowa (Bajang Institute, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in promoting regional economic growth, creating employment opportunities, and improving community welfare. However, one of the major challenges faced by MSMEs is limited business capital, both from personal funds and external financing, which affects their ability to increase business income. This study aims to analyze the effect of personal capital on MSME income, the effect of loan capital on MSME income, and the simultaneous effect of personal and loan capital on the income of MSMEs in Kupang City. This research employed a quantitative approach with an associative research design. The study population consisted of MSME owners in Kupang City, with a sample of 100 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics version 26. The results indicate that personal capital has a positive and significant effect on MSME income, with a t-value of 3.874 and a significance level of < 0.001. Loan capital also has a positive and significant effect on MSME income, with a t-value of 5.547 and a significance level of < 0.001. Furthermore, the simultaneous test reveals that personal capital and loan capital jointly have a positive and significant effect on MSME income, with an F-value of 24.417 and a significance level of < 0.001. The coefficient of determination (R²) of 0.335 indicates that personal capital and loan capital explain 33.5% of the variation in MSME income, while the remaining 66.5% is influenced by other factors not included in the research model. These findings provide empirical support for Production Theory and Capital Theory, which emphasize capital as a critical factor in enhancing business income. The study also offers practical implications for MSME owners and local governments in improving capital management and access to financing to support MSME development. Future research is recommended to include additional variables affecting MSME income and to expand the geographical scope of the study to obtain more comprehensive findings